Analisis Pembentukan Portofolio Optimal pada Indeks Saham LQ-45 dengan Metode Safety First Criterion - Amalia, Disya Recita; Sulistianingsih, Evy; Imro'ah, Nurfitri (Jambura Journal of Mathematics, 2024)
An optimal portfolio of stocks is a combination of various stock investment assets chosen to provide the maximum level of return for a specified level of risk or provide a minimal level of risk for a specified level of return. Investors form an optimal stock portfolio with the aim of minimizing the risk of investment activities. This research discusses the formation of the optimal portfolio on LQ-45 index stocks with the Safety First Criterion method. There are three criteria in the Safety First method, namely Roy Safety First, Kataoka Safety First, and Telser Safety First. The three criteria of Safety First have the main similarity in focusing on investment risk and have different objectives. The optimal portfolio with Roy Safety First criteria aims to reduce the possibility of a high level of risk. Then, the optimal portfolio with Kataoka Safety First criteria, has the goal of maximizing returns, with a level of risk determined by investors. While the optimal portfolio of Telser Safety First criteria aims to achieve the highest expected return within a predetermined risk level. The data in this study are secondary data on the weekly closing price of the LQ-45 index for the period February 2021 to January 2023, which is 105 weeks. Based on the results of the analysis, the optimal portfolio formation for risk-loving investors is the Telser criteria portfolio. This portfolio consists of ADRO, BBNI, BMRI, ITMG, and MEDC stocks. Then, the optimal portfolio for risk-averse investors is the Roy criteria portfolio consisting of ADRO, BBNI, BMRI, MDKA, and MEDC stocks.